'Numbers in Safety' for Pedestrians in Melbourne - Vidumini Pamuditha; David Levinson (Findings)
The 'Safety in Numbers' (SIN) phenomenon suggests that pedestrian presence enhances the safety conditions of a street or an intersection. The inverse relationship, which we call 'Numbers in Safety' (NIS), hypothesises that safer streets attract more pedestrians. This study tests the relationship using a panel regression analysis on six years (2014-2019) of data from 21 intersections in the Melbourne CBD. We find a consistent negative correlation between the changes in safety from the previous year and the current number of pedestrians, supporting the NIS hypothesis. An increase of one pedestrian fatal or serious injury crash at an intersection leads to nearly 139,000 fewer pedestrians in the following year.